Factors affecting the performance of micro, small and medium enterprises (MSMEs) in Denpasar - Suryathi, Ni Wayan; Gorda, Anak Agung Ngurah Oka Suryadinatha; Sunariani, Ni Nyoman; Sumantri, I G. A. N. Alit; Aditya, Gd. Ngurah Indra Arya; Indraswari, I Gusti Agung Ayu Pramita; Putra, I Gde Agoes Caskara Surya (International research journal of management, IT and social sciences, 2022)
The purpose of this study was to determine and analyze the factors that influence the performance of Micro, Small and Medium Enterprises (MSMEs) in Denpasar. The method of determining the sample used in this study is a purposive sampling technique. The sample size uses the Slovin formula to get a representative number of samples. The type of data used in this study is quantitative data and the data source used in this research is primary data source. Data was collected through questionnaires and then measured using a Likert scale. The questionnaire was tested using validity and reliability tests. The data analysis technique used is as follows: classical assumption test by performing normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination test, t-test (partial) and F-test. Based on the results of data analysis and discussion, it can be concluded that the factors that affect the performance of MSMEs in Denpasar during the Covid-19 pandemic are financial literacy and the effectiveness of the use of BPUM funds. Financial literacy has a significant positive effect on the performance of MSMEs with a t coefficient of 4.245, a regression coefficient of 0.300 and a significance of 0.000.